Application of the Environmental Design Treatments in the Steps of Design Process - Younis Mahmood Saleem; Sura Zakaria Y. Mahmood (Iraqi Journal of Architecture and Planning, 1970)
Due to the cyclical changes of the climate during the year, it is imperative in the building design process that special consideration and treatments should be taken in order to protect the building from the climatic changes. These treatments should be used in the designing process in order to upgrade the building so that it should be highly efficient in its thermal control and accomplish the desired comfort to the occupants.The multiplicity of the environmental treatments used in design and the wide spectrum of its effect that differ in accordance with the strategic target that was used for, resulted that its somewhat difficult for designer to be adequate by basic knowledge necessary in dealing with these treatments in the design.The research finds conclusion that correlate the environmental design treatments with the thermal control strategies (for hot and cold seasons) and the steps of the design process. These conclusions stressed the importance of having a programmable theoretical order of the environmental design treatments to produce thermally efficient buildings.